An amphiphilic fluorescent polymer combining aggregation-induced emission monomer and ε-polylysine for cell imaging. (October 2017) - Xie, Gaoyi; Ma, Chunping; Zhang, Xiqi; Liu, Hongliang; Gong, Jialiang; Zhao, Shuyang; Li, Yang; Wang, Ke; Wei, Yen
Abstract: An amphiphilic fluorescent polymer (Ply-EP3 ) combining an aggregation-induced emission monomer and ε-polylysine was prepared through epoxy ring-opening polymerization. 1 H NMR, FT-IR, and X-ray photoelectron spectra were conducted to characterize its chemical property. Such amphiphilicPly-EP3 could assemble into nanoparticles in water and form fluorescent polymeric nanoparticles (FPNs) with high water dispersibility. Dynamic light scattering result ofPly-EP3 FPNs demonstrated the size distribution of 106 ± 8 nm with the polydispersity index of 0.268. Transmission electron microscopy image ofPly-EP3 FPNs showed spherical nanoparticle morphology with a size range of 50–100 nm. The optical property of FPNs indicated intense green fluorescence with a fluorescence quantum yield of 33%. ThePly-EP3 FPNs further proved excellent stability with low critical micelle concentration of 0.042 mg mL −1 . The prepared FPNs also revealed high photostability after UV light irradiation for 120 min. Such FPNs showed excellent biocompatibility as the cells retained high viability at the concentration range of 10–120 μg mL −1 ofPly-EP3 for an incubated period of 12 h or 24 h, and exhibited excellent performance for cell imaging. Thanks to the high-performancePly-EP3 FPNs, including bright fluorescent emission, high water dispersibility and particle stability, and excellent photostability, this work provide an approach to prepare robust cross-linked biocompatible fluorescent polymers for cell imaging. Highlights: An amphiphilic fluorescent polymer was prepared. The polymer contained aggregation-induced emission fluorogen and ε-polylysine. The polymers formed fluorescent polymeric nanoparticles (FPNs) in water. The FPNs showed low critical micelle concentration. The FPNs exhibited high photostability and excellent biocompatibility.